An analysis of crisis services accessibility of new Francophone arrivals in the city of Winnipeg - Buisse, Diane M.N. (2006)
Abstract The purpose of this practicum project was to facilitate access to mental health services and those health services that address issues causing emotional distress for new Francophone non English-speaking arrivals in the City of Winnipeg. The objectives were 1) to uncover Francophone mental health and specialized health resources in the city of Winnipeg, 2) to identify barriers, attitudes, and access issues pertaining to Francophone services, 3) to develop a directory of Francophone resources and links for health care professionals and other essential providers, and 4) to develop recommendations for future study and consideration. The project was implemented through telephone interviewing of 24 administrators and direct providers in 19 agencies that provided mental health and specialized health services, as well as refugee and immigration agencies. The study used qualitative methods and a semi-structured survey interview design. Via analysis of the results, the project presents an argument that language barriers are indeed preventing access to care for Francophone immigrants, refugees and international students in the City of Winnipeg. This was widely stated by participants from key organizations that work with this aggregate population on an occasional to a frequent basis. It is also evident that, with use of Bachrach’s Continuity of Care Dimensions/Principles, continuity of care for this population is equally compromised because of language barriers, lack of culturally sensitive providers, and lack of Francophone providers.